2001
DOI: 10.1080/09637480120044138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of total energy expenditure in a Chinese population by a physical activity questionnaire: examination of validity

Abstract: A physical activity questionnaire from which total daily energy expenditure (TEE) could be estimated was developed for adult Hong Kong Chinese subjects, and its reliability and validity examined. The questionnaire was based on questionnaires used in Caucasians, and adapted for local lifestyle after focus group meetings involving subjects of all age groups. The questionnaire was administered to 94 subjects, consisting of healthy adults, the elderly, and two patient groups (those with renal disease on continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…There have not been detailed prior studies looking specifically at nonexercise movement in the healthy elderly population. Questionnaire-based studies have identified that age is inversely related to energy expenditure for occupation, that women may overvalue housework/caretaking activities in questionnaires, and that the utility in assessing free-living activity with questionnaires may still need to be established (3,11,21,36). There is one study focusing on nocturnal nonexercise movement in healthy elderly subjects that utilizes a wrist-worn activity monitor, suggesting that there is no effect of age in males on nocturnal nonexercise movment and that the duration of nocturnal immobility periods for females is greater than in males (47).…”
Section: Discussionmentioning
confidence: 99%
“…There have not been detailed prior studies looking specifically at nonexercise movement in the healthy elderly population. Questionnaire-based studies have identified that age is inversely related to energy expenditure for occupation, that women may overvalue housework/caretaking activities in questionnaires, and that the utility in assessing free-living activity with questionnaires may still need to be established (3,11,21,36). There is one study focusing on nocturnal nonexercise movement in healthy elderly subjects that utilizes a wrist-worn activity monitor, suggesting that there is no effect of age in males on nocturnal nonexercise movment and that the duration of nocturnal immobility periods for females is greater than in males (47).…”
Section: Discussionmentioning
confidence: 99%
“…The Impact on Participation and Autonomy (IPA) 39 The Impact on Participation and Autonomy Questionnaire (IPAQ) 38 The Physical Activity and Disability Survey (PADS) 155 The Physical Activity Questionnaire 117 The Quality of Well-Being Scale, Version 1.04 (QWB) 96 The Sickness Impact Profile (SIP) 20 Work Limitations Questionnaire (WLQ) 112 Human Activity Profile …”
Section: Assessment Of Function55mentioning
confidence: 99%
“…Of these 35 questionnaires, 7 enabled estimation of the metabolic equivalent or energy cost and 2 were able to be selfadministered (the Physical Activity Questionnaire and the Physical Activity Scale for the Elderly). However, the Physical Activity Questionnaire [23] has 55 questions, and the Physical Activity Scale for the Elderly has only 12 items which is an important consideration for reasons of participant burden.…”
Section: Introductionmentioning
confidence: 99%